Characteristics of Accessory Carpal Bone Fractures in 50 Racing Greyhounds - Johnson, K. A.; Piermattei, D. L.; Davis, Ph. E.; Bellenger, Ch. R. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
Fifty racing greyhounds with fracture of the accessory carpal bone presented to the Veterinary Teaching Hospitals at The University of Sydney (n = 35) and Colorado State University (n = 15) were reviewed for the purpose of identifying the frequency of the various fracture types, and to suggest possible factors which predispose to the injuries. All but three fractures occurred while the dogs were racing. All dogs raced on elliptical tracks in a counterclockwise direction, and this was implicated in the pathogenesis and anatomical distribution of these fractures.
Keywords: Accessory carpal bone; Greyhounds; Fractures